What local people? Examining the Gállok mining conflict and the rights of the Sámi population in terms of justice and power. Issue 86 (November 2017) - Persson, Sofia; Harnesk, David; Islar, Mine
Highlights: The mining conflict in Gállok is a struggle over social status and recognition. Historical injustices prevailing in institutions are underlying causes for conflict. Misrecognition can be institutional practices that subordinate indigenous people. Economic growth discourses obstruct the social legitimacy of less tangible values. Abstract: The global extraction of minerals is commonly located in areas populated by indigenous people; and while conflicts between multinational corporations and local activists and indigenous people are widespread today, the understanding of their dynamics are lacking. The Swedish government's encouragement to an expanding mining industry has caused resistance due to environmental and social implications, particularly its effect on Sámi reindeer husbandry. The resistance to a mine in Gállok is based on the belief that the right to decide about land use historically falls on the Sámi people, and the right to affect land use is detrimental for the survival of Sámi culture and reindeer husbandry. Although the conflict may be perceived as concerning access to natural resources, we argue that the perceived environmental conflict can be viewed as part of a larger struggle over social status and recognition. Data have been collected using qualitative methods such as observations, interviews and documents. The subsequent analysis relies on a meta-theoretical framework of justice as recognition using a typology of relations of power. Our findings suggest that relations of power constitute different categories of social actors. Stakeholders like the Sámi population are subordinated to more dominant stakeholders such as the government, the company and media, who have 'more' power or 'different' kinds of power 'over' others. Through these asymmetric power relations, historical state-Sámi relations are continuously reproduced within prevailing institutions, and also in this mining conflict. Interviewees from business and the municipality testified to the discourses driven by a neoliberal and profit-focused worldview. Challenging the neoliberal discourse, other stakeholders, namely civil society and Sámi, expressed an alternative discourse based on a local, traditional, cultural, environmental and anti-neoliberal worldview.